Associations of eicosapentaenoic acid and docosahexaenoic acid intakes with cardiovascular and all-cause mortality in patients with diabetes: Result from National Health and Nutrition Examination Survey 1999–2008 - Huang, Nian; Wang, Fang; Li, Shiyang; Zhai, Xiaobing; Ma, Wenzhi; Liu, Keyang; Sheerah, Haytham A.; Cao, Jinhong; Eshak, Ehab S. (Frontiers in Cardiovascular Medicine, 2023)
Introduction The evidence on eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) intake status and long-term mortality among people with diabetes is scarce. This study aimed to investigate the relationship between EPA and DHA intakes with all-cause and cause-specific mortality in adults with diabetes. Methods This study included 2,991 adults with diabetes from the National Health and Nutrition Examination Survey (NHANES) 1999–2008. Death outcomes were ascertained by linkage to the database records through 31 December 2015. Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for mortality from all causes, cardiovascular disease (CVD), and coronary heart disease (CHD) in patients with diabetes. Results Among 2,991 patients with diabetes, the mean age was 61.9 years (55.2% males). During the mean follow-up duration of 9.4 years, a total of 1,091 deaths were documented, of which 273 were due to CVD, including 227 CHD deaths. EPA and DHA intakes were associated with lower mortality risks, especially that of CVD. After adjusting for demographic, major lifestyle factors, overall dietary intake patterns, and history of hypertension and dyslipidemia, the multivariable HRs (95% CIs) of mortality risk comparing Q4 to Q1 of EPA intake were 0.55 (0.33–0.92; P-trend = 0.019) for CHD, 0.55 (0.36–0.83; P-trend = 0.005) for CVD, and 0.91 (0.70–1.18; P-trend = 0.264) for all-cause. The respective HRs (95% CIs) comparing Q4 to Q1 of DHA were 0.60 (0.37–0.98; P-trend = 0.051) for CHD, 0.58 (0.38–0.89; P-trend = 0.014) for CVD, and 0.92 (0.72–1.18; P-trend = 0.481) for all-cause. In subgroup analysis, we found that the association trends of EPA and DHA intakes with death risk remained robust among patients with diabetes, especially among those who are old, female, those with higher BMI, and dyslipidemia patients with CVD and CHD. Discussion In the USA, higher EPA and DHA intakes were associated with a lower risk of CHD and CVD mortality in patients with diabetes. Our study supports the benefits of adequate EPA and DHA intakes in promoting the health of patients with diabetes.